(untitled) (Iranian Journal of Kidney Diseases, 2011)
Introduction. Angiotensin-converting enzyme (ACE) gene polymorphisms have been studied in different ethnic populations. We assessed the ACE gene insertion/deletion alleles frequencies and genotype distributions in a group of individuals from among the general population of west Azarbaijan, Iran, in order to determine the prevalence of deletion/deletion (D/D), deletion/insertion (D/I) and insertion/insertion (I/I) genotypes. Materials and Methods. In a cross-sectional study, 167 healthy individuals were enrolled in a randomized fashion. They were selected from the general population of west Azerbaijan, Iran. Polymerase chain reaction was carried out to determine the ACE D/D, D/I and I/I genotypes. Results. The ACE alleles were D and I in 59.7% and 40.3% of the women, 59.3% and 40.7% of the men and 59.6% and 40.4% of all of the participants, respectively. The D/D, D/I, and I/I genotypes were observed in 22 (40.7%), 20 (37%), and 12 (22.2%) men, 41 (36.3%), 53 (46.9%), and 19 (16.8%) women, and 63 (37.7%), 73 (43.7%), and 31 (18.6%) participants, respectively. Statistical analysis showed that differences in ACE D and I alleles and genotype frequencies were not significant between the men and the women. Conclusions. In this study on the general population of west Azarbaijan, the frequencies of the ACE D and I alleles were 59.6% and 40.4%. The ACE D/D, D/I and I/I genotypes were seen in 37.7%, 43.7%, and 18.6% of the studied population, respectively.